Recognizing prior learning in vocational education and training: global ambitions and actual implementation in four countries. Issue 1 (2nd January 2023) - Maurer, Markus
ABSTRACT: This article contributes to a better theoretical understanding of the social processes underlying the development and implementation of schemes to improve the recognition of prior learning (RPL) in vocational education and training (VET). It traces the global diffusion of RPL, and then analyses the formulation of RPL policies and design and implementation of RPL schemes in four case study countries (Bangladesh, North-Macedonia, Sweden and Switzerland). The article draws on historical institutionalism and Margaret Archer's work on educational change to argue that the design and implementation of RPL schemes are strongly dependent on the status of VET qualifications in education systems and labour markets.